If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -6) + 2 = 3x + -11 Reorder the terms: 3(-6 + x) + 2 = 3x + -11 (-6 * 3 + x * 3) + 2 = 3x + -11 (-18 + 3x) + 2 = 3x + -11 Reorder the terms: -18 + 2 + 3x = 3x + -11 Combine like terms: -18 + 2 = -16 -16 + 3x = 3x + -11 Reorder the terms: -16 + 3x = -11 + 3x Add '-3x' to each side of the equation. -16 + 3x + -3x = -11 + 3x + -3x Combine like terms: 3x + -3x = 0 -16 + 0 = -11 + 3x + -3x -16 = -11 + 3x + -3x Combine like terms: 3x + -3x = 0 -16 = -11 + 0 -16 = -11 Solving -16 = -11 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -[5-(a+1)]=9-[(2a-3)] | | 3(5c-1)2=13c+3 | | 3(x-6)=x-19 | | 14n-8=24 | | c=4x+5 | | X^4+10X^2+18=0 | | 3x-18=6x+21 | | 58.5=35x-6 | | a(12-n)= | | 9z+4-7z=49-7z | | 2(-3p-6)=3[-4p-3(p+2)] | | 28+36+6(-7x+x)=2(5x-6) | | -4p-5=15 | | -16tx^2+21x-6=0 | | 6(a-8)+16=4(a-7) | | 6x-4(6-x)=2 | | Cot3x/5=-1 | | 28+36+6(-7x+c)=2(5x-6) | | 32+2x=12-7x | | 5(4x-2)+6=-3 | | 3(c-1)+4=17-(c-4) | | -8-5y-5=11-9y-16 | | -1=6-2(3y+2) | | 4x-50=4-5x | | A=x+3+z | | 4.5z=4.5z-6.25+6 | | 5x+19=x+21 | | 15-5x=-7x+15 | | 4x+16-6=22+6 | | 2y^2=13y | | 11=7+2(3z+2) | | -5x=-7+2x |